Preventing falls in hospitalized elderly: design and validation of a team intervention - Luís Filipe Correia da Cunha; Cristina Lavareda Baixinho; Maria Adriana Henriques
ABSTRACT Objective The objective of the present study was the design and validation, by a panel of experts, of a team intervention to manage the risk of falls in the hospitalized elderly. Method The method used was a quanti-qualitative approach, using the Delphi method. The study was developed in two phases: in the first, five researchers designed the intervention; in the second, 13 professionals validated it. Results The analysis of the content of the intervention designed by the participants in the first phase of the study allowed assignment of the indicators to the following previously defined categories: team formation; communication; leadership; monitoring; and mutual support. After two rounds, all the indicators obtained a consensus higher than 80%. Conclusion The present study allowed validation of a team intervention by a panel of experts, so that teams can manage the risk of falls in hospitalized elderly. The reliability test results ensure that the intervention can be used safely in clinics and for research.